DAMPAK INDUSTRI TERHADAP KUALITAS HIDUP MASYARAKAT DI SEKITAR KAWASAN INDUSTRI DI KABUPATEN MOROWALI - Afdhaliah K. Usman; Andrea E. Pravitasari; Sugeng A. Putranto (EnviroScienteae, 2023)
Industry is one of the pillars of strategic economic growth and can directly have a positive or negative impact on various aspects. This study discusses the influence of the presence of the industry in Morowali Regency on the quality of life of the community which is assessed from environmental and public health aspects. This research is combined research (Mixed Method) using primary and secondary data which is analyzed using several analytical tools, including Spatial Analysis, and descriptive analysis to describe the quality of life of each indicator based on secondary data and public perception, as well as the Renk Kendall Correlation Test with SPSS (Statistical Package for The Social Sciences) program to describe the impact of industry on people's quality of life. Based on the analysis, it is known that the industry has an impact on the quality of life of the community around the industry. This is evidenced by the results of the correlation, namely the value of the correlation coefficient between noise and quality of life reaches 36%. While the condition of river water with quality of life has a correlation coefficient of 16.6%, a significant correlation also occurs with quality of life with traffic flow, which is 22.65%.